Non-steroidal anti-inflammatory drugs on core body temperature during exercise: A systematic review - Dawn M. Emerson; Stephen CL. Chen; Melani R. Kelly; Bryant Parnell; Toni M. Torres-McGehee (Elsevier, 2021)
Background/Objective: Because of their anti-pyretic effects, some individuals prophylactically use non-steroidal anti-inflammatory drugs (NSAIDs) to blunt core temperature (Tc) increases during exercise, thus, potentially improving performance by preventing hyperthermia and/or exertional heat illness. However, NSAIDs induce gastrointestinal damage, alter renal function, and decrease cardiovascular function, which could compromise thermoregulation and increase Tc. The aim of this systematic review was to evaluate the effects of NSAIDs on Tc in exercising, adult humans. Methods: We conducted searches in MEDLINE, PubMed, Cochrane Reviews, and Google Scholar for literature published up to November 2020. We conducted a quality assessment review using the Physiotherapy Evidence Database scale. Nine articles achieved a score ≥ seven to be included in the review. Results: Seven studies found aspirin, ibuprofen, and naproxen had no effect (p > .05) on Tc during walking, running, or cycling for ≤ 90 min in moderate to hot environments. Two studies found significant Tc changes. In one investigation, 81 mg of aspirin for 7-10 days prior to exercise significantly increased Tc during cycling (p < .001); final Tc at the end of exercise = 38.3 ± 0.1 °C vs. control = 38.1 ± 0.1 °C. In contrast, participants administered 50 mg rofecoxib for 6 days experienced significantly lower Tc during 45 min of cycling compared to placebo (NSAID Tc range ≈ 36.7-37.2 °C vs control ≈ 37.3-37.8 °C, p < 0.05). Conclusions: There are limited quality studies examining NSAID effects on Tc during exercise in humans. The majority suggest taking non-selective NSAIDs (e.g., aspirin) 1-14 days before exercise does not significantly affect Tc during exercise. However, it remains unclear whether Tc increases, decreases, or does not change during exercise with other NSAID drug types (e.g., naproxen), higher dosages, chronic use, greater exercise intensity, and/or greater environmental temperatures.